Upper Extremity Compartment Syndrome in a Patient with Acute Gout Attack but without Trauma or Other Typical Causes - John G. Skedros; James S. Smith; Marshall K. Henrie; Ethan D. Finlinson; Joel D. Trachtenberg (Case Reports in Orthopedics)
We report the case of a 30-year-old Polynesian male with a severe gout flare of multiple joints and simultaneous acute compartment syndrome (ACS) of his right forearm and hand without trauma or other typical causes. He had a long history of gout flares, but none were known to be associated with compartment syndrome. He also had concurrent infections in his right elbow joint and olecranon bursa. A few days prior to this episode of ACS, high pain and swelling occurred in his right upper extremity after a minimal workout with light weights. A similar episode occurred seven months prior and was attributed to a gout flare. Unlike past flares that resolved with colchicine and/or anti-inflammatory medications, his current upper extremity pain/swelling worsened and became severe. Hand and forearm fasciotomies were performed. Workup included general medicine, rheumatology and infectious disease consultations, myriad blood tests, and imaging studies including Doppler ultrasound and CT angiography. Additional clinical history suggested that he had previously unrecognized recurrent exertional compartment syndrome that led to the episode of ACS reported here. Chronic exertional compartment syndrome (CECS) presents a difficult diagnosis when presented with multiple symptoms concurrently. This case provides an example of one such diagnosis.